IMPROVING CRITICAL THINKING ABILITIES IN SOCIAL STUDIES LEARNING USING THE PROBLEM BASED LEARNING (PBL) MODEL USED BY AUDIO VISUAL MEDIA IN ELEMENTARY SCHOOL STUDENTS - Alia Sopiatul Azkia; Arifin Maksum; Herlina Usman (Universitas Majalengka, 2025)
The Problem Based Learning model is a learning model that focuses on problem solving so as to stimulate critical thinking skills. The purpose of this study is to improve critical thinking skills in grade V students of SD Negeri Ciptasari I Pangkalan in social studies learning with the Problem Based Learning approach. This type of research is Classroom Action Research with data collection techniques using observation techniques, written tests, and documentation. The research is divided into three cycles, each cycle is divided into several stages; 1) Planning; 2) Implementation; 3) Observation; 4) Reflection. The results of this study are, Implementation of learning with the PBL approach in three stages, namely initial activities, core activities, and closing. In the pre-cycle the number of students who met the minimum criteria was 5 students with a percentage of 35% of all students, in cycle I it increased to 7 students with a percentage of 50%, and in cycle III it increased by 12 students with a percentage of 85.7%. Teacher and student observation sheets increased in each cycle. Teacher observation in cycle I reached 77%, cycle II 88%, cycle III 92%. Student observation sheets in cycle I 65%, cycle II 77%, cycle III increased to 85%. Based on these results, it can be concluded that the critical thinking skills of fifth grade students in social studies learning can be increased through the application of the Problem Based Learning (PBL) model assisted by audiovisual media.